Artistic features of the memory of the smell in the novel «Blood and Sweat» by Abdizhamil Nurpeisov - Japanova М.Е. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2018)
The purpose of this article is a comprehensive study of the olfactory space of trilogy in AbdizhamilNurpeisov’s trilogy “Blood and Sweat”, as well as the definition of the key role of odor images in the poetics of the art.It is the element of the images-smells that organizes the identity of the social and ethnic color of the existence of heroes - the inhabitants of the coast of the Aral Sea. The existence of individual, ethnic, family-related, professional, civil. As a result of the analysis of the poetics of the Kazakh writer’s artistic prose, various images-smells are revealed, all of them are historically and ethnically conditioned and functionally significant. So in the work the images-smells anthropomorphic, gastronomic, subject-real, spatial (the sea, steppe, dwellings, a city, aul) are pointed out.